Der Teeanbau in Neuguinea.: Landschaftswandel und Raumplanung im östlichen Teil des Zentralgebirges der Tropeninsel - Schweinfurth, Ulrich (ERDKUNDE, 1970)
Tea-plantations and native small holder schemes in the highlands of the Territory of Papua and New Guinea are a very recent venture; the upper Wahgi Valley round about Mount Hagen township has emerged as the centre for this new industry, though experimental plots have been established in various parts of the territory. The rapid expansion of the area under tea was made possible by the constant efforts of the Government Experimental Tea Station, Garaina, in providing the necessary bulk of teaseed, without which the entire enterprise clearly would not have been possible. Tea-cultivation in the upper Wahgi Valley is peculiar as it contradicts the rules of the pundits, being based on very unorthodox, pioneering methods: the main area under tea is concentrated in completely flat country, formerly continuously flooded by the meandering Wahgi River, on recently drained peat soils. The ultimate success of tea in the highlands of New Guinea depends on the political future of the Trust Territory, that is, the Eastern half of the island; only if there are fair prospects for a stable political development will the necessary capital be available. Given these preconditions, the author does not hesitate to predict a tremendous future for tea in the highlands of New Guinea; in the upper Wahgi Valley in particular certain beneficial, i.e. flavour improving influences, seem to be present, their possible impact well-known from the highlands of Ceylon - but it will take a long time to find out about this in the entirely new venture in the upper Wahgi Valley. Meanwhile, the immediate concern for good bulk quantity and quality seems, undoubtedly, to be assured. The establishment of the tea industry in the upper Wahgi Valley with Mount Hagen as the natural metropolis, at least for the Western Highland District, urgently calls for immediate planning operations for the entire area to safeguard future success, so easily in the balance, if nothing is done in time.